Diaspora as Cultures of Cooperation : Global and Local Perspectives - Carment, David; Sadjed, Ariane (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book examines the dynamic processes by which communities establish distinct notions of 'home' and 'belonging'. Focusing on the agency of diasporic groups, rather than (forced or voluntary) dispersion and a continued longing for the country of origin, it analyses how a diaspora presence impacts relations between 'home' and host countries. Its central concern is the specific role that diasporas play in global cooperation, including cases without a successful outcome. Bridging the divide between diaspora studies and international relations, it will appeal to sociologists, scholars of migration, anthropologists and policy-makers.
Keywords: Social sciences.; International organization.; Globalization.; Ethnology.; Social structure.; Social inequality.; Emigration and immigration.; Self.; Identity (Psychology).; elektronické knihy; electronic books